Wide‐Field Optical Microscopy of Microwave Fields Using Nitrogen‐Vacancy Centers in Diamonds. Issue 7 (11th May 2016) - Shao, Linbo; Liu, Ruishan; Zhang, Mian; Shneidman, Anna V.; Audier, Xavier; Markham, Matthew; Dhillon, Harpreet; Twitchen, Daniel J.; Xiao, Yun‐Feng; Lončar, Marko
Abstract : Real‐time wide‐field optical microscopy and spectroscopy of microwave fields is demonstrated using nitrogen‐vacancy (NV) centers in diamonds. By monitoring electron spin dependent fluorescence of NV centers under a continuous illumination, a microwave field is imaged with an amplitude sensitivity of ≈45 nT Hz −1/2 and a frequency sensitivity of 2.5 kHz Hz −1/2, across a 200 × 200 μm 2 imaging area with submicrometer spatial resolution.